Effect of Hydrostatic Pressure on the Refractive Indices of Some Solids - Waxler, R. M. (J Res Natl Bur Stand A Phys Chem, 1965)
Measurements were made on refractive index changes with hydrostatic pressures between 1 bar and 1 kbar using the helium yellow line. The materials studies were: KBr, NaCl, LiF, diamond, MgO, quartz, Al(2)O(3), and three silicate glasses. All the materials increased in refractive index with pressure except diamond, MgO, and Al(2)O(3) which decreased, and LiF which did not change. The results were compared with photoelastic measurements, and Pockel’s geometric theory of photoelasticity was substantiated as well as Mueller’s physical theory. The data show that the ratio of change of polarizability with density is greater for solids having stronger interatomic repulsive forces. Volume and temperature coefficients of polarizability were evaluated for the cubic crystals and glasses. The thermo-optic behavior of crystals and glasses is discussed.